Knockdown of S100A4 impairs arecoline-induced invasiveness of oral squamous cell carcinomas. Issue 7 (July 2015) - Hu, Fang-Wei; Lee, Shiuan-Shinn; Yang, Li-Chiu; Tsai, Chung-Hung; Wang, Tong-Hong; Chou, Ming-Yung; Yu, Cheng-Chia
Highlights S100A4 was positively correlated with clinical grading and lymph node metastasis of OSCC. Targeting S100A4 reversed arecoline-induced invasiveness in oral epithelial cells. S100A4 as therapeutic target for OSCC.